Cortical and brainstem plasticity in Tourette syndrome and obsessive‐compulsive disorder. Issue 12 (3rd July 2014) - Suppa, Antonio; Marsili, Luca; Di Stasio, Flavio; Berardelli, Isabella; Roselli, Valentina; Pasquini, Massimo; Cardona, Francesco; Berardelli, Alfredo
Abstract Gilles de la Tourette syndrome is characterized by motor/vocal tics commonly associated with psychiatric disorders, including obsessive‐compulsive disorder. We investigated primary motor cortex and brainstem plasticity in Tourette patients, exposed and unexposed to chronic drug treatment, with and without psychiatric disturbances. We also investigated primary motor cortex and brainstem plasticity in obsessive‐compulsive disorder. We studied 20 Tourette patients with and without psychiatric disturbances, 15 with obsessive‐compulsive disorder, and 20 healthy subjects. All groups included drug‐naïve patients. We conditioned the left primary motor cortex with intermittent/continuous theta‐burst stimulation and recorded motor evoked potentials. We conditioned the supraorbital nerve with facilitatory/inhibitory high‐frequency stimulation and recorded the blink reflex late response area. In healthy subjects, intermittent theta‐burst increased and continuous theta‐burst stimulation decreased motor evoked potentials. Differently, intermittent theta‐burst failed to increase and continuous theta‐burst stimulation failed to decrease motor evoked potentials in Tourette patients, with and without psychiatric disturbances. In obsessive‐compulsive disorder, intermittent/continuous theta‐burst stimulation elicited normal responses. In healthy subjects and in subjects with obsessive‐compulsive disorder, the blink reflex late response area increased after facilitatory high‐frequency and decreased after inhibitory high‐frequency stimulation. Conversely, in Tourette patients, with and without psychiatric disturbances, facilitatory/inhibitory high‐frequency stimulation left the blink reflex late response area unchanged. Theta‐burst and high‐frequency stimulation elicited similar responses in drug‐naïve and chronically treated patients. Tourette patients have reduced plasticity regardless of psychiatric disturbances. These findings suggest that abnormal plasticity contributes to the pathophysiology of Gilles de la Tourette syndrome. However, obsessive‐compulsive disorder patients have normal cortical and brainstem plasticity. © 2014 International Parkinson and Movement Disorder Society